SOCIAL EXCLUSION OF DEMI-MONDAINE AND NYAI IN FRENCH AND INDONESIAN NOVELS - Arifah Arum Candra Hayuningsih (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
One of the interesting themes but not widely featured in Indonesian and French literatures in the 19th and 20th centuries is nyai and demi-mondaine. Both have a similar meaning, namely the mistress of a man from the upper-middle class. This study looks at the exclusions that occur in the lives of nyai and demi-mondaine in an Indonesian novel titled Bumi Manusia by Pramoedya Ananta Toer and a French novel titled La Dame aux Camélias by Alexandre Dumas (philosophers). The analysis was carried out using Fairclough’s critical discourse analysis approach to examine the exclusion process in the two novels, which describes the realities that occur in society. This study found that the mistresses are excluded primarily through labeling and stereotyping. Despite the exclusion from the discourse of ‘honor’ in society, the mistresses find their own way of surviving in a society that does not like them.Salah satu tema menarik namun tidak banyak ditampilkan dalam karya sastra Indonesia dan Prancis di abad 19 dan 20 adalah kehidupan nyai dan demi-monde. Keduanya memiliki pengertian yang hampir serupa, yakni perempuan simpanan dari seorang laki-laki kelas menengah ke atas. Sikap masyarakat yang cenderung merendahkan mereka dapat dipandang sebagai proses eksklusi. Penelitian ini menelusuri bagaimana ekslusi yang terjadi dalam kehidupan nyai dan courtesan di Indonesia dan Prancis seperti yang ada pada novel Bumi Manusia karya Pramoedya Ananta Toer dan novel La Dame aux Camélias karya Alexandre Dumas (fils). Analisis dilakukan dengan metode analisis wacana kritis dari Fairclough untuk melihat proses eksklusi di kedua novel tersebut, yang merupakan gambaran dari realita yang terjadi di masyarakat. Penelitian ini memperlihatkan bahwa proses eksklusi paling banyak terjadi melalui labelling dan stereotyping. Meski demikian, para perempuan simpanan yang mengalami eksklusi dari wacana ‘kehormatan’ di masyarakat memiliki cara sendiri untuk bertahan di tengah masyarakat yang tidak menyukai mereka.